2011
DOI: 10.1111/j.1939-1676.2011.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Prevalence ofBartonella,Babesia, and HemotropicMycoplasmasp. in Dogs with Splenic Disease

Abstract: Background: Among diseases that cause splenomegaly in dogs, lymphoid nodular hyperplasia (LNH), splenic hemangiosarcoma (HSA), and fibrohistiocytic nodules (FHN) are common diagnoses. The spleen plays an important role in the immunologic control or elimination of vector-transmitted, blood-borne pathogens, including Bartonella sp., Babesia sp., and hemotropic Mycoplasma sp.Objective: To compare the prevalence of Bartonella sp., Babesia sp., and hemotropic Mycoplasma sp. DNA in spleens from dogs with LNH, HSA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 49 publications
(86 reference statements)
3
47
0
Order By: Relevance
“…Similarly, blood samples were analyzed for the presence of Bartonella spp. using the Bartonella alphaproteobacterial growth medium (BAPGM) enrichment culture PCR as described previously (16)(17)(18). DNAs from naive dog and human blood extracted at the same time and in the same manner were used as negative controls for the PCR testing.…”
mentioning
confidence: 99%
“…Similarly, blood samples were analyzed for the presence of Bartonella spp. using the Bartonella alphaproteobacterial growth medium (BAPGM) enrichment culture PCR as described previously (16)(17)(18). DNAs from naive dog and human blood extracted at the same time and in the same manner were used as negative controls for the PCR testing.…”
mentioning
confidence: 99%
“…Recent in vivo evidence supporting a role for B. vinsonii subsp. berkhoffii in vasoproliferative lesions has been generated by amplifying and sequencing the bacteria's DNA from a spectrum of vasoproliferative lesions in dogs, including hemangiopericytoma [26], bacillary angiomatosis [27], and hemangiosarcoma [14]; from cats with systemic reactive angioendotheliomatosis (this study); and from EHE human patients [26,28]. PCR amplification or isolation of B. vinsonii subsp.…”
Section: Discussionmentioning
confidence: 99%
“…DNA, including B. vinsonii subsp. berkhoffii, has recently been amplified and sequenced from dogs with splenic hemangiosarcomas [14]. Collectively, these observations suggested that B. vinsonii subsp.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations